Double-walled carbon nanotube/polymer nanocomposites: Electrical properties under dc and ac fields - Yakuphanoğlu, Fahrettin; Yahia, I. S.; Barim, G.; Senkal, B. Filiz (Elsevier Science Sa, 2010)
The electrical properties of the poly(methyl methacrylate:carbon nanotubes nanocomposites) have been investigated by direct current conductivity and complex impedance spectroscopy methods. The direct current conductivity results of the poly(methyl methacrylate):carbon nanotube as a nanocomposites show that the electrical conductivity property of the poly(methyl methacrylate) changes from insulating state to semiconducting state with incorporation of double wall carbon nanotube DWCNTs into insulating polymer matrix. The alternating current conductivity mechanism of the nanocomposites is controlled by the correlated barrier hopping mechanism. The correlated barrier hopping CBH model for intimate valence alternation pairs IVAP's describes the conduction mechanism of PMMA doped with (1%) DWCNTs, while correlated barrier hopping CBH model for non-intimate valence alternation pairs describes the conduction mechanism of PMMA doped with (5% and 8%) DWCNTs. The real part of the complex impedance decreases with the increase of the applied frequency which revealed that the PMMA:DWCNT nanocomposites behaves like semiconducting materials. The complex impedance Nyquist plots for PMMA doped with different concentration DWCNTs over are characterized by the appearance of a single semicircular arc whose radii of curvature decreases with increasing the temperature. Cole and Cole plots show the presence of temperature dependent electrical relaxation phenomena in the PMMA:DWCNT nanocomposites. The obtained electronic parameters confirm that PMMA:DWCNTs exhibit organic semiconductor behavior. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: PMMA; Double wall carbon nanotubes (DWCNTs); Nanocomposites; Electrical properties (dc and ac)